Factors limiting reproductive success in terrestrial orchids - Mattila, Elisa (2000)
Resource and pollen availability are generally regarded as the most important factors limiting reproductive success of plants. Pollination limitation has been shown to play an especially important role in orchids with complicated pollination systems. However, resource availability may also affect reproductive success in perennial plants both directly and indirectly via pollinator attraction. In this thesis, I examine the importance of both pollen and resource availability to reproductive success in nectarless and nectar-producing orchid species. I also examine how the position within an inflorescence affects reproductive traits of individual flowers. Reproductive success of nectarless Dactylorhiza incarnata was found to be primarily pollination-limited within a year, while in nectar-producing Platanthera bifolia, reproductive success was limited by both pollinator services and resources. A decrease in photosynthetic area following artificial defoliation resulted in decreased seed production, but had no effect on pollen production in Dactylorhiza maculata and P. bifolia. Defoliation had no effect on spur length or nectar production in P. bifolia, but the defoliated plants were found to have lower pollination success than the non-defoliated plants. In D. maculata, inhibition of photosynthesis in both leaves and the photosynthetically active green parts of the inflorescence resulted in decreased seed production. Likewise, inhibition of function of mycorrhizal fungi affected seed production negatively. The underground corm was found to be an important source of resources in this species. In D. maculata flower size, pollen production and capsule weight decreased towards the top of inflorescence. Decrease in flower size and pollen production may be caused by architectural effects, but seed production of the uppermost flowers was found to be limited by resource availability. Changes in resource availability and allocation to capsule production did not affect growth and reproduction of P. bifolia in the following year. However, in D. incarnata heavy allocation to reproduction in one year resulted in decreased probability of flowering in the following year. In D. maculata, defoliation decreased leaf area and the amount of resources stored in the underground corm. This difference in life-history traits between rewarding and deceptive species may be due to uncertainty of pollination in the nectarless species.